2019
DOI: 10.1186/s40468-019-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

Rater attitude towards emerging varieties of English: a new rater effect?

Abstract: Background: A strong interest in researching World Englishes (WE) in relation to language assessment has become an emerging theme in language assessment studies over the past two decades. While research on WE has highlighted the status, function, and legitimacy of varieties of English language, it remains unclear how raters respond to the results of the global spread of English. Also unclear is whether their attitudes towards the varieties of English constitute a biasing factor in the scores they award in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…In contrast with the large number of studies conducted in these countries, however, there are only a few studies conducted in OC countries, particularly in South Asia. Among 43 recent AWEs studies published in international research journals between 2010 and 2020, only four studies were found to be conducted in the South Asian region (Bernaisch, 2012;Bernaisch & Koch, 2016) or foregrounded a South Asian variety (Hsu, 2019;Weekly, 2018).…”
Section: A Proliferation Of Studies In Expanding Circle Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the large number of studies conducted in these countries, however, there are only a few studies conducted in OC countries, particularly in South Asia. Among 43 recent AWEs studies published in international research journals between 2010 and 2020, only four studies were found to be conducted in the South Asian region (Bernaisch, 2012;Bernaisch & Koch, 2016) or foregrounded a South Asian variety (Hsu, 2019;Weekly, 2018).…”
Section: A Proliferation Of Studies In Expanding Circle Contextsmentioning
confidence: 99%
“…Experts in the study of language attitudes like Garret (2010) have pointed out that one of the key assumptions in the ABC model, the causal link between language attitudes, emotions, beliefs and behaviours, has not been satisfactorily established, and thus remains controversial (Garrett, 2010). However, the assumption that a greater awareness of a variety leads to a positive attitude or acceptance of the variety continues to undergird many of the recent AWEs studies conducted in pedagogical contexts (Ahn, 2015;Almagren, 2018;Chan, 2018;Hsu, 2019;Lee, 2019;Sadeghpour & Sharifian, 2017Tsu & Chen, 2014;Wang, 2014). These studies often implicitly and explicitly emphasise the need to develop awareness among teachers and learners, particularly of low-prestige varieties of English, to address negative attitudes towards them, and also to temper the unquestioning demand for IC norms in the classroom.…”
Section: A Causal Link Assumed Between Attitudes Beliefs and Behavioursmentioning
confidence: 99%